(untitled) (The Review of Diabetic Studies, 2025)
Emergency medical services (EMS) are a cornerstone of modern healthcare systems, and paramedics play a pivotal role in saving lives through rapid assessment, stabilization, and transport of critically ill or injured patients. In Saudi Arabia, the Vision 2030 reform agenda has prioritized healthcare transformation, emphasizing quality, accessibility, and patient-centered emergency response. This systematic review explores the evolving role of paramedics within the Saudi emergency care framework, highlighting their contributions to prehospital management, trauma care, cardiac emergencies, and disaster response. Peer-reviewed studies published between 2016 and 2025 were analyzed to assess paramedic competencies, training programs, technological integration, and inter-professional collaboration. Findings reveal significant progress in prehospital response capabilities, expanded educational standards, and the adoption of digital tools such as AI-enabled triage and tele-EMS systems. However, challenges persist regarding workforce distribution, gender inclusion, and continuous professional development. This review underscores the strategic role of paramedics as catalysts for healthcare transformation in Saudi Arabia and provides policy recommendations to enhance national EMS effectiveness and sustainability.